Ревизия рода Hyptioxesta (Lepidoptera, Noctuidae) с описанием нового вида - Кононенко, В.С. (Вестник зоологии, 1984)
A Revision of the Genus Hyptioxesta (Lepidoptera, Noctuidae) with Description of a New Species. Kononenko V. S.— Vestn. zool., 1984, No. 1 The genus Hyptioxesta is transferred from subfamily Acontiinae to Noctiinac. H. hurenizool sp. n. is described from Sikhote-Alin Mts. It differs from similar H. penthima Ersch. by paler wing colouration, diffused wing pattern, straight second band, absence of terminal stripe on hind wing underside and by genitalic characters. Estimata magadanica Kononenko is transferred to the genus Hyptioxesta.